Experimental investigation on self-loosening of a bolted joint under cyclical temperature changes - Oybek Maripjon Ugli Eraliev; Yi-He Zhang; Kwang-Hee Lee; Chul-Hee Lee (Advances in Mechanical Engineering, 2021)
The most commonly used part in engineering fields is threaded fasteners. There are a lot of advantages of fasteners. One of them is that they can be easily disassembled and reused, but a bolted joint can loosen easily when a transversal load is applied. The clamp load of a bolted joint can also loosen slowly when subjected to repeated temperature changes. This paper presents an experimental investigation of the self-loosening of bolted joints under cyclical temperature variation. Experiments are carried out under several cyclical temperature changes with different bolt preloads. Rectangular threaded bolted joints with M12 × 1.75 bolts and nuts are tested in a specially designed testing apparatus. Material of bolt, nut, and plates is a stainless steel. The experimental results show that the high initial bolt preload may prevent the joint from self-loosening and the bolted joint has loosened significantly in the first cycle of temperature changes. From this investigation, the loosening of the bolted joint can be considered as a first stage self-loosening.